(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Kadir NN, Husain AAA, Irmawati, Priosambodo D, Jamal M, Ilyas M, Malkab ANI, Fasirah E, Moore AM. 2022. Short Communication: Rare grouper Epinephelus miliaris from market surveys in South Sulawesi, Indonesia. Biodiversitas 23: 6070-6074. Groupers of the genusEpinephelus are tropical demersal fishes of both ecological and economic importance. However, knowledge is still limited regarding the diversity of fish caught and traded as well as the fine-scale distribution of many species. During a series of market surveys to photograph and identify groupers exploited in South Sulawesi, Indonesia, a small number of specimens of a widespread but rare grouper, Epinephelus miliaris, were found. The purpose of this study was to contribute to the body of knowledge on E. miliaris by analyzing and presenting spatial, morphological, and meristic data collected on these specimens and discussing the findings with respect to the current state of knowledge regarding this species. Our findings add Sulawesi, including the Makassar Strait and Gulf of Bone, to the recorded distribution of E. miliaris, to the south of the range according to the International Union for Conservation of Nature (IUCN) Red List. Both specimens were within the juvenile or sub-adult size range for this species. We conclude that there is a need to re-evaluate the range of this species, specifically within Indonesia, in fisheries and fish biodiversity databases.